COVID-19 pandemic in Southeast Asia: intervention and mitigation efforts - Muhammad Ashraf, Fauzi; Norazha, Paiman (Emerald Group Publishing Ltd., 2020)
Purpose: Coronavirus disease 2019 (COVID-19) has sent shockwaves throughout the world in less than two months. Countries in South East Asia are not spared in this plight. As the disease can be transmitted from human to human, extensive control and mitigation efforts have been taken by almost every country where the disease has been reported. Southeast Asian countries or the Association of Southeast Asian Nations (ASEAN), being one of the closest regions with China, have taken various measures to slow down and contain the spread of the pandemic virus. Design/methodology/approach: Multiple strategies have been taken by the government to reduce the number of infections in the region. This includes phases of lockdowns in affected areas and federal order to close businesses to reduce the rate of infection among the people. As ASEAN comprises diverse cultures, socioeconomic backgrounds and geographical differences, steps taken are definitely based on what are deemed important and applicable to each country. Findings: This paper reviews what has been taken by each of the ASEAN members and further recommendations that can be taken to ensure the issue of human security in the region can be preserved. Originality/value: The originality of this paper is to show mitigation and prevention strategies undertaken by ASEAN nation in combating COVID-19.